1994
DOI: 10.1111/j.1476-5381.1994.tb16189.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel antagonist, phenylbenzene ω‐phosphono‐α‐amino acid, for strychnine‐sensitive glycine receptors in the rat spinal cord

Abstract: 1 3-[2'-Phosphonomethyl[1,1'-biphenyl]-3-yl]alanine (PMBA) is a novel glycine antagonist at strychnine-sensitive receptors. The chemical structure of PMBA, possessing both a glycine moiety and a phosphono group, is quite different from that of strychnine.2 In the spinal motoneurone of newborn rats, glycine (100 gmM-1 mM) induced depolarizing responses in a concentration-dependent manner. PMBA effectively inhibited depolarizing responses to glycine and other agonists, such as taurine and P-alanine. The dose-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…Treatment with strychnine enhanced PS amplitude in both the DLS and nAc suggesting that glycine receptors are tonically activated and exert a net inhibitory control of excitatory input. This finding was also confirmed in slices treated with PMBA, which has been reported not to interact with α 7 nicotinic acetylcholine, NMDA, or GABA A receptors when used at concentrations below 100 μM (Saitoh et al, 1994;Renna et al, 2007). The glycine receptor can be activated by glycine, taurine, and β-alanine, and microdialysate sampling from the nAc has shown that all three agonists are present at measurable levels during baseline conditions (Lidö et al, 2009;Adermark et al, 2011).…”
Section: Glycinergic Modulation Of Excitatory Input and Extracellularsupporting
confidence: 65%
“…Treatment with strychnine enhanced PS amplitude in both the DLS and nAc suggesting that glycine receptors are tonically activated and exert a net inhibitory control of excitatory input. This finding was also confirmed in slices treated with PMBA, which has been reported not to interact with α 7 nicotinic acetylcholine, NMDA, or GABA A receptors when used at concentrations below 100 μM (Saitoh et al, 1994;Renna et al, 2007). The glycine receptor can be activated by glycine, taurine, and β-alanine, and microdialysate sampling from the nAc has shown that all three agonists are present at measurable levels during baseline conditions (Lidö et al, 2009;Adermark et al, 2011).…”
Section: Glycinergic Modulation Of Excitatory Input and Extracellularsupporting
confidence: 65%
“…Although the possibility cannot be entirely ruled out that the antagonistic effect of strychnine on nicotinic agonists-induced antiallodynic effect might be due to the association of strychnine with α7 nAChR, we speculate that this possibility does not seem to hold true in this study for the following reasons. The affinity of strychnine to α7 nAChR is much lower than that to glycine receptors, for examples, Ki for strychnine as an inhibitor of the α7 nAChR and glycine receptors were found to be approximately 680 nM and 32 nM, respectively (Anand et al, 1993;Saitoh et al, 1994). Moreover, the IC 50 for strychnine to block α4β2 nAChR-stimulated currents in hippocampal neurons was about 118 μM (Matsubayashi et al, 1998).…”
Section: Discussionmentioning
confidence: 94%
“…Two other antagonists of GlyRs, phenylbenzene ω‐phosphono‐α‐amino acid at 100 μ m (PMBA) (Saitoh et al 1994) and ginkgolide B at 1 μ m (Betz & Laube, 2006) caused a similar, statistically significant, reduction of glycine‐induced currents (PMBA: 56.8 ± 10.5, n = 9, and ginkgolide B: 33.9 ± 13.1, n = 6) (Fig. 2).…”
mentioning
confidence: 80%